2007
DOI: 10.1177/112067210701700322
|View full text |Cite
|
Sign up to set email alerts
|

Serum Prolactin Levels and Behçet Disease

Abstract: Results suggest the role of prolactin in BD pathogenesis and its association with disease expression, especially in complete-type BD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…The relationship between BD and PRL had also been studied (5)(6)(7)(8)(9) and were found to be related to disease activity in some of the reports (5, 6), but the results are conflicting. None of these studies categorized the patients considering their sex, making it impossible to compare the difference of PRL levels between female and male patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The relationship between BD and PRL had also been studied (5)(6)(7)(8)(9) and were found to be related to disease activity in some of the reports (5, 6), but the results are conflicting. None of these studies categorized the patients considering their sex, making it impossible to compare the difference of PRL levels between female and male patients.…”
Section: Discussionmentioning
confidence: 99%
“…There are little data on serum hormone concentrations of female patients with BD and most of these studies are about possible relationship of prolactin on BD pathogenesis or disease activity (5)(6)(7)(8)(9). Although some of these studies suggest a possible role for this immunoregulatory hormone in the disease expression and pathogenesis (5,6), no such correlation has been found in several others (7)(8)(9).…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…[11] In some studies, it has been suggested that there is a correlation between high serum prolactin levels and BD activity. [5,12] The elevated levels of prolactin may contribute to disease activity by augmenting immune processes. Proença et al [12] suggested that prolactin can play a role in BD pathogenesis and disease expression, especially in complete-type BD.…”
Section: Discussionmentioning
confidence: 99%
“…In one of these studies Çil et al found no significant difference in terms of hormone levels between the Behcet and control groups [10]. However in another study, Proençha et al reported that serum prolactin levels were significantly higher in BD patients versus controls [11]. Another study by Atasoy et al also had declared that patients with active BD had higher serum prolactin levels than the inactive and control groups.…”
Section: Behcet's Disease and Hypophysismentioning
confidence: 99%